Fragments Of The Gospel From The Private Archive Of Dadeshkeliani Kept In The National Centre Of Manuscripts - Shatirishvili, Lela (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
The collection of the museum and a new fund (Q) of the former historical ethnographic society (H) of the Georgian national centre of manuscripts keep the two fragments on parchment from Gospel of Luke ( 10-12th centuries ). The interest to them was aroused by the copy of the letter sent by Kalistrate Tsintsadze to Akaki Shanidze in 1943, concerning the Gospel taken apart into three papers each from the palace of Dadianis’ in the 1910s. Among the reconsidered fragments of the existing Gospels the attention was focused on Q-783, and the exploration for finding similar parts revealed 6 pages of the same Gospel, enclosed under H-1445. The fragments were identified on the basis of the paleographical and textological factors. Q-783 appears to be the central part of H-1445. Parts of the paper fragments are palimpsests. The lower layer of the three belongs to the 10th century, and that of the fourth is a “khan-meti “(„khan“-prevailed) text of the 7th century, including the scripture of the articles 19-25 of Chapter 20 of John. The copy used as an original one is replete with old scripts. The fragments attract attention in codicological and textological respects.